Assessment of Safety and Efficacy of Tofacitinib, Stratified by Age, in Patients from the Ulcerative Colitis Clinical Program - Lichtenstein, Gary R; Bressler, Brian; Francisconi, Carlos; Vermeire, Severine; Lawendy, Nervin; Salese, Leonardo; Sawyerr, Gosford; Shi, Hongjiong; Su, Chinyu; Judd, Donna T; Jones, Thomas; Loftus, Edward V (Inflammatory bowel diseases, 2023)
Abstract Background In patients with ulcerative colitis (UC), risks of infection and malignancies increase with age. Tofacitinib is an oral, small molecule Janus kinase inhibitor for the treatment of UC. This analysis assessed age as a risk factor for adverse events of special interest (AESI) in the tofacitinib UC clinical program. Methods Data were from phase 2 and 3 induction studies, a phase 3 maintenance study, and an open-label, long-term extension study. Efficacy and/or safety outcomes were analyzed in the Induction, Maintenance, and Overall Cohorts (patients who received ≥ 1 dose of tofacitinib), stratified by age. The effects of baseline demographic and disease-related factors on AESI incidence were assessed by Cox proportional-hazards regression analysis. Results In the Overall Cohort (1157 patients with ≤ 6.8 years’ tofacitinib treatment), age was a statistically significant predictor of herpes zoster (HZ), malignancies excluding nonmelanoma skin cancer (NMSC), and NMSC. Other statistically significant predictors included prior tumor necrosis factor inhibitor failure for HZ, NMSC, and opportunistic infection events, and prior duration of UC for malignancies excluding NMSC. In the Induction and Maintenance Cohorts, a higher proportion of tofacitinib-treated than placebo-treated patients (numerical difference) achieved the efficacy endpoints (endoscopic improvement, clinical remission, clinical response) across all age groups. Conclusions Older individuals receiving tofacitinib as induction and maintenance therapy to treat UC may have an increased risk of HZ, malignancies (excluding NMSC), and NMSC versus similarly treated younger patients, consistent with findings from the general population. Across all age groups, tofacitinib demonstrated greater efficacy than placebo as an induction and maintenance therapy. ClinicalTrials.gov Registration Numbers NCT00787202; NCT01465763; NCT01458951; NCT01458574; NCT01470612. Lay Summary Age was assessed as a risk factor for adverse events of special interest in the tofacitinib ulcerative colitis clinical program. Older individuals receiving tofacitinib may have an increased risk of herpes zoster, malignancies (excluding nonmelanoma skin cancer), and nonmelanoma skin cancer versus similarly treated younger patients. Graphical Abstract Graphical Abstract